Effect of comorbid migraine on propranolol efficacy for painful TMD in a randomized controlled trial. (June 2021) - Tchivileva, Inna E; Ohrbach, Richard; Fillingim, Roger B; Lim, Pei Feng; Giosia, Massimiliano Di; Ribeiro-Dasilva, Margarete; Campbell, John H; Hadgraft, Holly; Willis, Janet; Arbes, Samuel J; Slade, Gary D
Introduction: The migraine-preventive drug propranolol is efficacious in reducing pain from temporomandibular disorder, suggesting potential modifying or mediating effects of comorbid migraine. Methods: In this randomized controlled trial, myofascial temporomandibular disorder patients were treated with propranolol or placebo for 9 weeks. The primary endpoint was change in a facial pain index derived from daily symptom diaries. Linear and logistic regression models tested for a migraine × treatment-group interaction in reducing facial pain index. Counterfactual models explored changes in headache impact and heart rate as mediators of propranolol's efficacy. Results: Propranolol's efficacy in reducing facial pain index was greater among the 104 migraineurs than the 95 non-migraineurs: For example, for the binary ≥ 30% reduction in facial pain index, odds ratios were 3.3 (95% confidence limits: 1.4, 8.1) versus 1.3 (0.5, 3.2), respectively, although the interaction was statistically non-significant ( p  = 0.139). Cumulative response curves confirmed greater efficacy for migraineurs than non-migraineurs (differences in area under the curve 26% and 6%, respectively; p  = 0.081). While 9% of the treatment effect was mediated by reduced headache impact, 46% was mediated by reduced heart rate. Conclusions: Propranolol was more efficacious in reducing temporomandibular disorder pain among migraineurs than non-migraineurs, with more of the effect mediated by reduced heart rate than by reduced headache impact. Study identification and registration: SOPPRANO; NCT02437383;https://clinicaltrials.gov/ct2/show/NCT02437383